Burden of informal caregivers of chronic respiratory failure patients in Croatia : Opterećenost neformalnih njegovatelja osoba s kroničnim respiratornim zatajenjem u Hrvatskoj - Benko, Snježana (Array, 2021)
The aim of this study was to determine the level of burden of informal caregivers of chronic respiratory failure patients measured by the Zarit Burden Interview Questionnaire (ZBI) and to identify overburdened informal caregivers who can become hidden patients. We recruited the respondents in two hospitals for lung disease and a home healthcare service in Zagreb during 2020. After they had been identified as primary informal caregivers who provided high intensity informal care for more than six months, they were asked to complete the Croatian version of the ZBI questionnaire and a questionnaire on sociodemographic characteristics. We used descriptive methods for statistical analysis in this cross-sectional study. We presented the data in tables as absolute frequencies, percentages and measures of the central tendency, and graphically by using diagrams. The study included 150 informal caregivers. The majority were female, over 50 years of age with high school education. The largest percentage of informal caregivers was retired. The highest scores were given to the statements on worrying about future and patient dependency while the lowest scores were given to the statements on leaving the care to someone else and feelings such as anger or embarrassment caused by the patient. The results of this study show that more than half of informal caregivers of chronic respiratory failure patients are moderately to severely burdened.